Virological failure of patients on maraviroc-based antiretroviral therapy. (19th February 2015) - Raymond, Stéphanie; Maillard, Anne; Amiel, Corinne; Peytavin, Gilles; Trabaud, Mary Anne; Desbois, Delphine; Bellecave, Pantxika; Delaugerre, Constance; Soulie, Cathia; Marcelin, Anne Geneviève; Descamps, Diane; Izopet, Jacques; et al.
Abstract: Objectives: Virological failure (VF) in patients on maraviroc-based treatment has been associated with altered HIV tropism and resistance to maraviroc. This multicentre study aimed to characterize VF in patients treated with maraviroc. Methods: We analysed 27 patients whose treatment failed between 2008 and 2011. They had been screened for HIV tropism before maraviroc initiation using population-based V3 genotyping. HIV-1 tropism and resistance of R5 viruses to maraviroc at VF and at baseline were determined retrospectively using an ultrasensitive recombinant virus assay (RVA). Results: Viruses from 27 patients given maraviroc on the basis of the R5 genotype were characterized at the time of treatment failure. The RVA indicated that 12 patients harboured CXCR4-using viruses and 15 (56%) had pure R5 viruses at failure. One-third of those harbouring CXCR4-using viruses (4/12) were infected with R5X4/X4 viruses according to the RVA before maraviroc initiation. We analysed the phenotypic resistance to maraviroc of four patients harbouring R5 viruses at failure; two harboured viruses whose maximum percentage inhibition was reduced by 65%–90%, while the other two were infected with susceptible viruses. All patients had effective concentrations of drugs. Conclusions: Half of the maraviroc-treated patients who experienced VF harboured CXCR4-using viruses at failure, one-third of them were detected by a phenotypic method before maraviroc initiation. Phenotypic assessment of R5 virus resistance to CCR5 antagonists at failure could help optimize antiretroviral therapy.